The puzzle of papules over face and extrafacial areas: A rare case of disseminated idiopathic T-Cell pseudolymphoma - Sumit A Hajare; Vaishali H Wankhade; Gitesh U Sawatkar; Rajesh Pratap Singh (Wolters Kluwer Medknow Publications, 2021)
Papular lesions over face have a wide range of differential diagnoses. The clinical differentiation among these is difficult and often requires clinicopathological correlation. We hereby report the case of a 28 year old female presenting with numerous skin colored papular lesions over face, pinna and upper limbs.